Estimated prevalence of erosive tooth wear in permanent teeth of children and adolescents: An epidemiological systematic review and meta-regression analysis. Issue 1 (January 2015) - Salas, M.M.S.; Nascimento, G.G.; Huysmans, M.C.; Demarco, F.F.
Abstract Objectives The main purpose of this systematic review was to estimate the prevalence of dental erosion in permanent teeth of children and adolescents. Methods An electronic search was performed up to and including March 2014. Eligibility criteria included population-based studies in permanent teeth of children and adolescents aged 8–19-year-old reporting the prevalence or data that allowed the calculation of prevalence rates of tooth erosion. Data collection assessed information regarding geographic location, type of index used for clinical examination, sample size, year of publication, age, examined teeth and tissue exposure. The estimated prevalence of erosive wear was determined, followed by a meta-regression analysis. Results Twenty-two papers were included in the systematic review. The overall estimated prevalence of tooth erosion was 30.4% (95%IC 23.8–37.0). In the multivariate meta-regression model use of the Tooth Wear Index for clinical examination, studies with sample smaller than 1000 subjects and those conducted in the Middle East and Africa remained associated with higher dental erosion prevalence rates. Conclusions Our results demonstrated that the estimated prevalence of erosive wear in permanent teeth of children and adolescents is 30.4% with high heterogeneity between studies. Additionally, the correct choice of a clinical index for dental erosion detection and the geographic location play an important role for the large variability of erosive tooth wear in permanent teeth of children and adolescents. Clinical significance The prevalence of tooth erosion observed in permanent teeth of children and adolescents was considerable high. Our results demonstrated that prevalence rate of erosive wear was influenced by methodological and diagnosis factors. When tooth erosion is assessed, the clinical index should be considered.